Synthesis of the Tetracyclic Core (ABCE Rings) of Daphenylline - Fang, Bowen; Zheng, Huaiji; Zhao, Changgui; Jing, Peng; Li, Huilin; Xie, Xingang; She, Xuegong (Journal of organic chemistry, 2012)
A concise synthesis of the tetracyclic core (ABCE rings) of daphenylline has been accomplished involving a benzobicyclo[3.3.1] lactam as the key intermediate. This bridged bicyclic intermediate was efficiently constructed via a Brønsted acid promoted intramolecular Friedel–Crafts type Michael addition of a δ-benzyl α,β-unsaturated δ-lactam.